(NsOWREMENNYJ RUSSKIJ QZYK (B:s (Nu^EBNOE POSOBIE (B/s - (NwALGINA(B, (NnINA sERGEEWNAs; (NrOZENTALX(B, (NdITMAR |LXQ[EWI^s; (NfOMINA(B, (NmARGARITA iWANOWNAs ((NmOSKWA (B:s (NwYS[AQ [KOLA(B,s, 1987)
(NbIBLIOGR(B.: (NS(B. 467-468s
(NnA PER(B. (NAWT(B. (NNE UKAZANYs
Keywords: (NrUSSKIJ QZYKs